AGRICULTURAL REFORM AND EMERGING CONFLICTS - Alimova Mokhichehra Muzafarovna (Galaxy International Interdisciplinary Research Journal, 2022)
This article presents information on land-water reform implemented in 1927-1929 in the Zarafshan Oasis, as well as processes related to the reform of agriculture. An appropriate analysis was carried out and scientific conclusions were made.